2019
DOI: 10.1111/1471-3802.12447
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of teachers of children with intellectual and developmental disabilities in inclusive schools in Accra, Ghana

Abstract: Although inclusive education is the best form of education for all children including those with disabilities, children with intellectual and developmental disabilities (IDD) in developing contexts such as Ghana are often educated in segregated settings or institutionalised. An understanding of teachers’ experiences with children with IDD in inclusion can inform strategies for more effective inclusive systems for children with IDD. We analysed the interview data from 16 general and two special educators who te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Based on the case study, it was found that at the microsystem level, and in particular, the binary relationship between teacher of special education and the mentally disabled student, the differentiated material contributed positively to the student's active participation in the syllabus (literacy curriculum) (Drossinou -Korea & Panopoulos, 2017). At the mesosystem level, it has been observed that special education teacher and collaboration with other adults is an essential prerequisite for effective teaching intervention (Okyere, Aldersey, & Lysaght, 2019). For example, in the present study the special education teacher worked with the school staff to shape the pupil's school history background and came into contact with her general teacher in order to set a common teaching objective and teaching steps for the History lesson which would be taught.…”
Section: Discussionmentioning
confidence: 87%
“…Based on the case study, it was found that at the microsystem level, and in particular, the binary relationship between teacher of special education and the mentally disabled student, the differentiated material contributed positively to the student's active participation in the syllabus (literacy curriculum) (Drossinou -Korea & Panopoulos, 2017). At the mesosystem level, it has been observed that special education teacher and collaboration with other adults is an essential prerequisite for effective teaching intervention (Okyere, Aldersey, & Lysaght, 2019). For example, in the present study the special education teacher worked with the school staff to shape the pupil's school history background and came into contact with her general teacher in order to set a common teaching objective and teaching steps for the History lesson which would be taught.…”
Section: Discussionmentioning
confidence: 87%
“…In Ghana, only a few studies have explored the attitudes of teachers toward specific disabilities. For instance, Okyere, Aldersey, and Lysaght (2019) conducted a qualitative study on the experiences of teachers teaching students with ID in regular classrooms in Ghana. Although the teachers reported positive experiences of teaching students with ID, especially when the students were able to grasp the concepts being taught, they had difficulty managing challenging behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…In China, improving inclusive education became the significant attention in China's educational system (Zhang, Rosen, Cheng, & Li, 2018). In Ghana, the government has committed to providing equal education opportunities for children with disabilities by implementing inclusive education (Okyere, Aldersey, & Lysaght, 2019). United States accepted inclusive education among the U.S general and special teachers, disability activists, and parents of children with disabilities (Tahir, Brian, & Michael, 2019) In Indonesia, inclusive education started with the trials in the year 1998-2001 in several Yogyakarta areas (Rasmitadila & Tambunan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One way to maximize inclusive education is by investigating students' perceptions with disabilities and regular students. It reflects how the government should develop inclusive education in the future from students who have been previously taken apart in inclusive education (Okyere et al, 2019). Investigating students also describe how students feel included in inclusive education and examine a new and innovative way to improve inclusive education (Schwab, Sharma, & Loreman, 2018).…”
Section: Introductionmentioning
confidence: 99%